Jump test indicates foot flexion may improve clap speed skate - Allinger, T. L.; Motl, R. W. (1998)
Results of the study demonstrate that the flexible shoe condition outperformed the three rigid shoe conditions. These jump tests indicate that a clap style speed skate that allows flexion of the foot at the metatarsal heads may outperform existing clap skates with a rigid base. An increase in energy of 50 J or 10 % (flexible vs. rigid, total energy) per stroke correspons appr. to a decrease in lap times of 0.9 s or 3% of world record times.